Answer:
Step-by-step explanation:
The graph that represents the function
f(x) = (x + 4)(x + 1)(x - 3)
crosses the x-axis three times: at x = -4, x = -1, and x = 3
because we apply the zero product rule and found the roots -4, -1, and 3
x+ 4= 0 → x = -4
x+1 = 0 → x = -1
x-3 = 0 → x = 3
Answer:
6 29/40
Step-by-step explanation:
1/8 times 5 equals 5/40 and 3/5 times 8 equals 24/40 you add them together to get 29/40 which can not be simplified then add 4 and 2 to get 6 so <u>6 29/40 </u>is your answer.
The product of -8. (-8)= 64
Ricky jogged 6 miles on tuesday and 6 miles on friday
<em><u>Solution:</u></em>
Given that,
Rick jogged the same distance on tuesday and friday
Let "x" be the distance jooged on each tuesday and friday
He also jogged for 8 miles on sunday
Total of 20 miles for the week
Therefore, we frame a equation as,
total distance jogged = miles jogged on tuesday + miles jogged on friday + miles jogged on sunday
20 = x + x + 8
20 = 2x + 8
2x = 20 - 8
2x = 12
x = 6
Thus Ricky jogged 6 miles on tuesday and 6 miles on friday
Answer:
2
y = -0.5x + 10.5
Step-by-step explanation:
put a negative sign and 1 on top of the number next to the x to get the line thats perpendicular
2
y = -0.5x + 10.5